The Concept of Negative Generalization in Islam through the Quran and Sunnah: Its Causes and Effects - Al-Daris, Bader Mohammad (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This research aims to investigate the concept of negative generalization linguistically and terminologically, illustrate its relationship with other sciences, and examine relevant Quranic verses and Hadiths and explain their connection to this issue. It also aims to identify its causes, and understand its effects on the Muslim community from the perspective of the sample. Furthermore, it seeks to draw recommendations that contribute to reducing this practice. Methods: This research adopts several methodologies, including the inductive approach and the descriptive-analytical approach. It connects and interprets information, clarifies the qualitative relationship between them, and draws conclusions. Results: The educational curricula in State institutions should comprise content that includes the tools of subjective, methodological and logical thinking. The curricula should also call to mind the warnings of Islamic law against negative generalization. Moreover, it is vital that the Ministry of Awqaf & Islamic Affairs in the State of Kuwait organize conferences and seminars to enable Imams and Islamic preachers to introduce a better understanding of the generalization concept and warn people of its repercussions. Conclusions: The scholarly value of this research lies in its serious examination of the concept of negative generalization through the Quran and Sunnah and its causes and effects. It employs an exploratory study method, and a systematic, descriptive, and inductive approach to determine the dimensions of this practice, in order to avoid its effects and prevent its causes.